A computer‐based Pinyin intervention for disadvantaged children in China: Effects on Pinyin skills, phonological awareness, and character reading. (8th March 2020) - Li, Yixun; Chen, Xi; Li, Hong; Sheng, Xiaotian; Chen, Liu; Richardson, Ulla; Lyytinen, Heikki
Abstract : Pinyin is an alphabetic script that denotes pronunciations of Chinese characters. Studies have shown that Pinyin instruction enhances both phonological awareness (e.g., Shu et al., Developmental Science, 2008, 11, 171–181) and character reading (e.g., Lin et al., Psychological Science, 2010, 21, 1117–1122) in Chinese children. In the present study, we provided a 3‐week Pinyin intervention with a computer‐based Pinyin GraphoGame to disadvantaged migrant children with poor Pinyin skills. A total of 252 first graders who were children of migrant workers in a large Chinese city were assessed to identify poor Pinyin readers. Fifty‐six 7‐year‐old children with poor Pinyin skills were selected and randomly divided into a training group and a control group, with 28 children in each group. The training group played the Pinyin GraphoGame for 3 weeks, while the control group received school instruction only during the same period. Results showed that the children in the training group outperformed their peers in the control group on Pinyin reading accuracy and fluency, onset–rime and phonemic awareness, and character reading. These results suggest that the Pinyin GraphoGame may be a cost‐effective method to enhance Pinyin and literacy outcomes for underprivileged children in China.